Notas sobre el género Phytolacca (Phytolaccaceae) en México - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2000)
The genus Phytolacca is a taxonomically difficult one and its classificatory arrangement is pending a thorough reappraisal. A study of more than 1100 collection numbers shows the existence in Mexico of five more or less reasonably distinct entities: P. americana L., P. icosandra L., P. rivinoides Kunth & Bouché, P. rugosa Braun & Bouché and P. thyrsiflora Fenzl ex J. A. Schmidt. Although several authors expressed their doubts concerning the presence of P. americana in Mexico, the study of abundant materials obtained in last decades reveals that this species extends its area along the moister places of the Sierra Madre Oriental, from Nuevo León and Tamaulipas to northern Oaxaca. Its Mexican populations are morphologically more variable than those of eastern United States and in such circumstances it is believed that the species may have originated in Mexico and subsequently colonized ecologically similar territories situated to the north. P. heterotepala H. Walt., distinguished on the basis of slightly zygomorphic perianths, only seems to comprehend cases of floral anomalies in individuals of P. icosandra and P. rugosa. P. icosandra and P. octandra L. are usually differentiated from each other in the number of stamens and in the length of the inflorescence. However, in central and southern Mexico numerous populations exist, in which plants do not adjust to this separation. Thus, in the expectation of a detailed study of this situation, only one taxon is recognized. Although P. rugosa differs from the remaining regional members of Phytolacca in its apically free carpels, its taxonomic situation and circumscription is not clear. In Mexico within this complex two groups of plants can be separated on the basis of their morphological and ecological affinities, one of them being much more similar to P. icosandra than the other, possibly under stronger genetic influence of the latter. Among the examined material several specimens show the trend toward inflorescence branching in its lower part. Three of these specimens do not differ in other characters from P. americana, P. rivinoides and P. rugosa, respectively, and are interpreted as sporadical variants of these species. Several possibly belong to P. thyrsiflora Fenzl ex J. A. Schmidt, an essentially South American species, the cirumscription of which remains to be defined. In terms of conclusions it can be proposed that future approximations to the taxonomy of Phytolacca reduce their dependence from the computation of stamen-numbers and incorporate more emphasis on the aspect of ecological affinities of the plants. More attention is also recommended to the possibility of incidence of floral anomalies and in view of the importance of birds as dispersers of Phytolacca seeds, the genetic consequences of long and medium-distance dispersal are to be considered.